174Yb 3P1 level relaxation found via weak magnetic field dependence of collision-induced stimulated photon echo. (3rd May 2018) - Rubtsova, N N; Gol'dort, V G; Khvorostov, E B; Kochubei, S A; Reshetov, V A
Abstract: Collision-induced stimulated photon echo generated at transition was analyzed theoretically and investigated experimentally in the gaseous mixture of ytterbium vapour diluted with a large amount of buffer gas xenon in the presence of a weak longitudinal magnetic field. The inter-combination transition of 174 Yb (6s 2 ) 1 S (6s6p) 3 P1 was used; all experimental parameters were carefully controlled for their correspondence to the broad spectral line conditions. The curve representing the collision-induced stimulated photon echo variations versus a weak magnetic field strength showed very good agreement with the corresponding theoretical curve; this agreement permitted getting the decay rates for 174 Yb level 3 P1 orientation and alignment in collisions with Xe.